Terorisme sebagai cabaran ideologi Muslim masa kini : satu analisis dari perspektif falsafah - Zul'Azmi Yaakob,; Ahmad Sunawari Long, (Universiti Kebangsaan Malaysia, 2015)
Terrorism is currently becoming an ideological challenge for Muslims in contemporary world. The rise of terrorist groups such as the Islamic State (IS) and others who claimed themselves as jihadist and propagates Islamic jihad similar to the idea of the medieval ‘Holy War’ not only target non-Muslims or kuffar, but also their Muslim brothers respectively. This act of terrorism raised dilemma among Muslim societies in general whether to support the extreme groups or to defy them as they portrayed themselves as representing the whole Muslims whereas in fact they only represent a group of disillusioned Muslims. This paper aims at analysing their ideological challenge from the philosophical point of view and Islamic ethics. Generally, this analysis emphasizes on the importance of Islamic ethics and law in order to achieve true understanding of jihad.